Pemanfaatan Media Visual dalam Pembelajaran Maharatul Kalam Pada Program Akselerasi Bahasa Arab di MTs eL-BAS (Lembaga Bina Anak Sholeh) Ciamis - holis; Abidin, Munirul; Kiswanto, Dudi; Rizki, Desy Maulani (Tarling : Journal of Language Education, 2023)
This research has the intention to describe how the implementation and benefits of visual media in learning Maharotul Kalam in the accelerated Arabic program at MTs eL-BAS Ciamis. This research is a field research that uses a qualitative research type methodology. The data in this study were collected through interviews and observation methods, through primary data sources, Arabic teachers and students of the MTs eL-BAS Ciamis language acceleration program. Data analysis was carried out using deductive qualitative, choosing a conceptual framework, collecting data, analyzing data and drawing conclusions. The results obtained from this study are the implementation and benefits of visual media in learning Maharotul Kalam in the Arabic acceleration program at MTs eL-BAS (bina anak sholeh institute) Ciamis in the form of increasing student enthusiasm in the learning process which facilitates understanding of some students, encourages active participation of students in learning, and support teachers in conveying material effectively. In an effort to use it, the teacher uses visual media in the form of Arabic phrase pamphlets (Ibaroh kosiroh), Arabic vocabulary cards (Mufrodat), and Arabic posters